Formation and growth of Pd nanoparticles in UiO-67 MOF by in situ EXAFS. (October 2020) - Kamyshova, E.G.; Skorynina, A.A.; Bugaev, A.L.; Lamberti, C.; Soldatov, A.V.
Abstract: We present a detailed extended X-ray absorption fine structure (EXAFS) characterization of the formation process of palladium nanoparticles (NPs) inside UiO-67 metal-organic framework (MOF). Starting from the initial UiO-67 structure with 10% of PdCl2 bpydc moieties with grafted Pd ions replacing standard 4, 4′-biphenyldicarboxylate linkers, we followed in situ H2 -temperature programmed reduction (TPR) of the material. The cleavage of Pd–N and Pd–Cl bonds and simultaneous growth of the Pd–Pd contribution of metal NPs start at 200 °C. Below 300 °C metal NPs are small and are constrained inside the cavities of UiO-67, while at higher temperatures, the Pd–Pd coordination number (CN) increases to its bulk values, implying the aggregation of NPs into big palladium particles with probable destruction of MOF crystal structure. The formation of bigger particles is also confirmed by non-linear dependence of Debye-Waller parameter (DW) for Pd‒Pd contribution upon temperature. Highlights: Pd NPs are formed inside UiO-67 pores in the temperature range from 200 to 300 °C. Pd NPs agglomerate to bulk particles above 300 °C, destroying UiO-67 crystallinity. Loosing of Pd‒N bonds starts earlier than that of Pd-Cl ones. Pd NPs inside UiO-67 pores have high structural disorder.